From the sea to the bee: Gellan gum-honey-diatom composite to deliver resveratrol for cartilage regeneration under oxidative stress conditions. (1st October 2020) - Bonifacio, Maria A.; Cochis, Andrea; Cometa, Stefania; Gentile, Piergiorgio; Scalzone, Annachiara; Scalia, Alessandro C.; Rimondini, Lia; De Giglio, Elvira
Highlights: Resveratrol loaded Gellan Gum-Diatoms-Honey composite scaffolds were developed. Scaffolds demonstrated mechanical properties suitable for cartilage regeneration. Resveratrol release in simulated synovial fluid was tuned by the composite scaffolds. In vitro tests confirmed the antioxidant activity of the scaffolds. Abstract: Carbohydrate-based porous scaffolds are promising biomaterials to support cartilage regeneration. In this respect, their composition could be designed to face clinical challenges, i.e., articular load bearing, infections and oxidative stress. Herein, an innovative scaffold has been developed, combining raw materials belonging to different kingdoms of life. Indeed, gellan gum, a bacterial-derived carbohydrate, was blended with a beehive product (Manuka honey) with prominent antibacterial features. Moreover, resveratrol, a phytoalexin with powerful antioxidant activity, was loaded into the silica shells of diatoms, unicellular microalgae with cytocompatible features. The developed composite porous scaffolds demonstrated mechanical properties suitable for cartilage regeneration. Furthermore, they allowed the controlled release of resveratrol, hindering bacterial proliferation and oxidative stress damage, while supporting stem cell colonization and chondrogenic differentiation.